Asuhan Kebidanan Continuity of Care (COC) pada Ny. N Umur 37 Tahun G3P2A0 - Tri Hidayani; Wahyu Kristiningrum (Universitas Ngudi Waluyo, 2024)
According to the World Health Organization (WHO), there are 500,000 maternal deaths (AKI) per year and 10,000,000 infant mortality (AKB), mainly among neonates in the world (Who, 2019). The number of maternal mortality in Semarang City from 2015 to 2020 has decreased from 128 / 100,000 KH to 71.35 / 100.000 KH. However, by 2021 AKI was 95.30 / 100.000 live births with a total of 21 cases, of which 16 cases died from Covid. By 2022, the number of mothers who died fell to 15 cases with AKI 67.25 per 100.000 KH (Profil Kesehatan, 2022). In Indonesia, the government has undertaken a reduction effort on AKI and AKB, one of them by running an integrated prenatal care program to sustainable care. (COC). One measure of the well-being of a nation is the health of mother and child. (KIA). Objective of the Case Study to perform the application of maternity orphanage Countinuity Of Care to the 37-year-old G3P2A0 pregnancy age 21 weeks in Bidan Siti Fatchiyah Karangjati District of Semarang. The method in this research the author uses data collection method using interviews, observations with primary and secondary data through the KIA Book, physical examination as well as this research began from December-May 2024 research instruments using the observation format, interview sheets and documentation studies in the form of maternity foster care format according to the guidelines. Based on the results of continuity of care in women during pregnancy, childbirth, infancy, newborns and family planning, obtained Mrs. 37 years old G3P2A0 pregnant 21 weeks not found any significant problems during the pregnancies, the delivery was carried out at the hospital Dr. Gondo Suwarno. Breathing is normal, no bleeding, good uterine contractions, lochea rubra, dry perinium wounds. The baby was born spontaneously, no abnormalities, the results of anthropometric examination were within normal limits, the SHK examination was already done. Ms. N decided to use the implants. Abstrak World Health Organization (WHO), ada 500.000 Angka Kematian Ibu (AKI) setiap tahun dan 10.000.000 Angka Kematian Bayi (AKB), terutama pada neonatus di dunia (WHO, 2019). Angka Kematian Ibu (AKI) di Kota Semarang sejak tahun 2015 hingga 2020 mengalami penurunan dari 128 / 100.000 KH menjadi 71,35 / 100.000 KH. Namun pada tahun 2021 AKI menjadi 95,30 / 100.000 kelahiran hidup dengan jumlah 21 kasus, dimana 16 kasus meninggal karena Covid. Pada tahun 2022 jumlah ibu yang meninggal turun menjadi 15 kasus dengan AKI 67,25 per 100.000 KH (Profil Kesehatan, 2022). Di negara Indonesia, pemerintah melakukan upaya penurunan pada AKI dan AKB, salah satunya dengan menjalankan program pelayanan antenatal terpadu hingga perawatan berkelanjutan Contiunity of Care (COC). Salah satu tolak ukur kesejahteraan suatu negara adalah kesehatan ibu dan anak (KIA). Tujuan dari Studi kasus untuk melakukan penerapan asuhan kebidanan Countinuity Of Care pada Ny. N Usia 37 Tahun G3P2A0 usia kehamilan 21 minggu di Bidan Siti Fatchiyah Karangjati Kabupaten Semarang. Metode dalam penelitian ini penulis menggunakan metode pengumpulan data yaitu menggunakan wawancara, observasi dengan data primer dan sekunder melalui Buku KIA, pemeriksaan fisik serta penelitian ini dimulai sejak bulan Desember-Mei 2024 instrumen penelitian menggunakan format observasi, lembar wawancara dan studi dokumentasi dalam bentuk format asuhan kebidanan sesuai pedoman. Berdasarkan hasil Asuhan Berkelanjutan (Continuity Of Care) pada Ny. N dari masa Kehamilan, Persalinan, Nifas, Bayi Baru Lahir dan Keluarga Berencana, didapatkan Ny. N usia 37 Tahun G3P2A0 hamil 21 minggu tidak ditemukan masalah yang signifikan selama masa kehamilan, persalinan dilakukan di RSUD dr Gondo Suwarno. Masa nifas berlangsung normal tidak ada pendarahan, kontraksi uterus baik, lochea rubra, luka perinium kering. Bayi lahir spontan, tidak ada kelainan, hasil pemeriksaan antropometri dalam batas normal, dilakukan pemeriksaan SHK. Ny. N memutuskan untuk menggunakan KB implant.